Early detection of microstructural white matter changes associated with arterial pulsatility - Jolly, Todd A.; Bateman, Grant A.; Levi, Christopher R.; Parsons, Mark W.; Michie, Pat; Karayanidis, Frini (Frontiers in Human Neuroscience, 2013)
Increased cerebral blood flow pulsatility is common in vascular dementia and is associated with macrostructural damage to cerebral white matter or leukoaraiosis (LA). In this study, we examine whether cerebral blood flow pulsatility is associated with macrostructural and microstructural changes in cerebral white matter in older adults with no or mild leukoaraiosis and no evidence of dementia. Diffusion Tensor Imaging was used to measure fractional anisotropy (FA), an index of the microstructural integrity of white matter, and radial diffusivity (RaD), a measure sensitive to the integrity of myelin. When controlling for age, increased arterial pulsation was associated with deterioration in both measures of white matter microstructure but not LA severity. A stepwise multiple linear regression model revealed that arterial pulsatility index was the strongest predictor of FA (R = .483, adjusted R2 = .220), followed by LA severity, but not age. These findings suggest that arterial pulsatility may provide insight into age-related reduction in white matter FA. Specifically, increased arterial pulsatility may increase perivascular shear stress and lead to accumulation of damage to perivascular oligodendrocytes, resulting in microstructural changes in white matter and contributing to proliferation of LA over time. Changes in cerebral blood flow pulsatility may therefore provide a sensitive index of white matter health that could facilitate the early detection of risk for perivascular white matter damage and the assessment of the effectiveness of preventative treatment targeted at reducing pulsatility.